MRI of the Achilles tendon—A comprehensive pictorial review. Part one. (2021) - Szaro, Pawel; Nilsson-Helander, Katarina; Carmont, Michael
Highlights: Presence of normal septation between subtendons may mimic an intrasubstance tear. MRI is superior to ultrasound in detection of partial tears. Ultrasound is as useful as MRI in detection of tendinopathy and full-thickness tears. Kager's fat pad is involved in infection more than in postoperative changes. The Achilles tendon xanthoma has a higher signal on T1- and T2-weighted sequences. Abstract: The normal Achilles tendon is composed of twisted subtendons separated by thin high signal septae, which are a potential pitfall on MRI because they mimic a tendon tear. Tendinopathy and full thickness tears may be assessed effectively both on MRI and ultrasound. MRI is superior to ultrasound in detection of partial tears and for postoperative assessment. The use of fat suppression sequences allows the ability to detect focal lesions. Sagittal and coronal sections are useful for assessing the distance between stumps of a ruptured tendon. Sequences with contrast are indicated in postoperative investigations and suspicion of infection, arthritis or tumor. MRI may reveal inflammatory changes with minor symptoms long before the clinical manifestations of seronegative spondyloarthropathy. The most common non-traumatic focal lesion of the Achilles tendon is Achilles tendon xanthoma, which is manifested by intermediate or slightly higher signal on T1- and T2-weighted images compared to that in the normal Achilles tendon. Other tumors of the Achilles tendon are very rare, whereas the involvement of the tendon from tumor in adjacent structures is more frequent. The novel MRI sequences may help to detect disorders of the Achilles tendon more specifically before clinical manifestation. Regeneration or remodeling of the Achilles tendon can be non‐invasively detected and monitored in diffusion tensor imaging. Assessment of healing is possible using T2-mapping while evaluating the tendon vascularization in intravoxel incoherent motion MRI.